Konstruksi dan Negosiasi Interseksionalitas dalam Seperti Dendam, Rindu Harus Dibayar Tuntas serta Implikasi Sugestif Nilai Pendidikan - Ilaturahmi, Auzi (Faculty of Languages and Arts, Universitas Negeri Padang, 2025)
The study that wants to be analyzed is how the construction and negotiation of intersectionality are built in “Seperti Dendam, Rindu Harus Dibayar Tuntas” and the suggestive implications of educational values. Therefore, the mimetic approach is used as the basis for analysis in this study. The social reality related to intersectionality reflected by the author in his novel entitled